WAYS TO ENSURE ECONOMIC GROWTH BASED ON INCREASING THE EFFICIENCY OF THE INDUSTRIAL SECTOR - Najimadinov Ravshanbek Dushamboyevich (Innovate Conferences, 2025)
Today, economic development is accelerating around the world. Every sector of the economy is experiencing this progress. In particular, the widespread use of information technologies has revolutionized economic development. Although global challenges such as pandemics, climate change, and geopolitical tensions significantly impact the economy, growth, particularly in the industrial sector, continues.